Academics’ conceptions of higher education decolonisation - Sibanda, J. (South African Journal of Higher Education, 2021)
The urgency for a decolonised university curriculum in South Africa, occasioned by student protests, demands interrogation of conceptions of decolonisation academic staff hold, seeing that the design and implementation of decolonised education rests largely with them. To determine the academics’ conceptions, the study adopted the interpretivist paradigm, using semi-structured interviews to solicit data from 13 purposively sampled academic staff at a South African university. Data analysis took a grounded analysis approach, where content analysed categories/themes emerged from the transcribed and coded data, not from apriori assumptions. Findings reflected both the conception of decolonisation as recentring and decentring. Findings also pointed to the ubiquitous use of the terms Africa and African(s) in defining decolonisation, conflating Afrocentric philosophy and Africanisation with decolonisation. Such findings represented the conception of decolonisation as a recentring of curriculum from the West to Africa as the centre. Other academics’ conceptions also represented a decentring of knowledge from Western hegemony without necessarily recentring it to African hegemony. Much advocacy was for achieving equality and parity between extant knowledges and hitherto marginalised local knowledges. There was also a manifest vacillation in respondents’ conception of decolonisation as they responded to the different questions, almost evincing a continuum between what can be termed a hard version and a soft version of the concept. The study recommends broader, intensive, institutional discussion of conceptual issues around curriculum decolonisation prior to implementation.issues around curriculum decolonisation prior to implementation.